Effect of Exotoxin a Isolated from Pseudomonas Aeruginosa Against Human Cancer Cell Lines - Muthanna Hamid Hassan (Institute of Medico-legal Publications Pvt Ltd, 2021)
In This study, the presence of Pseudomonas aeruginosa was investigated from many clinical samples, and then about 54 isolates were obtained, diagnosed with all different diagnostic methods, and then the bacterial isolates produced for Exotoxin A were detected by the ELISA method and then the most productive isolate was chosen for purification by means of Precipitation with ammonium sulphate and ion-exchange column and detection of molecular weight was (M.W 65.03KD).The competent isolation tested its toxicity against two cancer cell lines HeLa and PC3 which were an inhibition ratio 69.1% and 61.6% respectively in high concentration